The Effect of R&D Expenditures on Earnings Management: A Research on Bist-All Shares - Yasar Bayraktar; Asiye Tutuncu (Istanbul Business Research (IBR), 2020)
R&D expenditures are important in increasing the level of information and technological development. Efficiency in production, cost reduction and competitive advantage are achieved with the added value created by successful R&D activities. However, in the process of accounting and reporting the R&D expenditures, some manipulative applications can be implemented by the business management for achieving personal or corporate targets. The purpose of this research is to reveal the effect of R&D expenditures on earnings management. In this context, from 2007 to 2018, 65 companies that made R&D expenditures included in BIST-All Shares Index were examined. The earnings management effect calculated on the Modified Jones Model, taking into account the current period, one-year and two-year time lag of R&D expenditures was tested with panel data analysis. As a result of the research, it was determined that R&D expenditures negatively affect earnings management in the current period and positively in lagged periods. In addition, while size and leverage have negative effects on earnings management in the current period, one-year and two-year time lag, no statistically significant relationship was found in terms of return on assets.
Keywords: 650; R&D Expenditures; Earnings Management; Panel Data Analysis